2018
DOI: 10.1002/aps3.1147
|View full text |Cite
|
Sign up to set email alerts
|

Development of 15 nuclear microsatellite markers in Deuterocohnia (Pitcairnioideae; Bromeliaceae) using 454 pyrosequencing

Abstract: Premise of the StudyMicrosatellite markers were developed in Deuterocohnia longipetala (Bromeliaceae) to investigate species and subspecies boundaries within the genus and the genetic diversity of natural populations.Methods and ResultsWe used 454 pyrosequencing to isolate 835 microsatellite loci in D. longipetala. Of 64 loci selected for primer design, 15 were polymorphic among 23 individuals of D. longipetala and 76 individuals of the heterologous subspecies D. meziana subsp. meziana and D. meziana subsp. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The successful cross-amplification observed in this study (86% amplification and 46% polymorphism) was also reported for other bromeliads (Barbará et al 2007b;Palma-Silva et al 2007, 2009Paggi et al 2008;Wörhmann and Weising 2011;Zanella et al 2012;Goetze et al 2013;Lavor et al 2014;Aoki-Gonçalves et al 2014;Neri et al 2015;Ferreira et al 2017;Chaves et al 2018;Godoy et al 2018;Zenk et al 2018). The success of heterologous nuclear microsatellite transfer is usually related to the phylogenetic distance between tested taxa (Barbará et al 2007a).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The successful cross-amplification observed in this study (86% amplification and 46% polymorphism) was also reported for other bromeliads (Barbará et al 2007b;Palma-Silva et al 2007, 2009Paggi et al 2008;Wörhmann and Weising 2011;Zanella et al 2012;Goetze et al 2013;Lavor et al 2014;Aoki-Gonçalves et al 2014;Neri et al 2015;Ferreira et al 2017;Chaves et al 2018;Godoy et al 2018;Zenk et al 2018). The success of heterologous nuclear microsatellite transfer is usually related to the phylogenetic distance between tested taxa (Barbará et al 2007a).…”
Section: Resultssupporting
confidence: 82%
“…In the case of Bromeliaceae species, wide adaptive radiation has caused low levels of genomic divergence. Therefore, various researchers have been successfully transferring markers among species within subfamilies and even among subfamilies (Barbará et al 2007b(Barbará et al , 2009Palma-Silva et al 2007;Paggi et al 2008;Wörhmann and Weising 2011;Wörhmann et al 2012;Zanella et al 2012;Goetze et al 2013;Ferreira et al 2017;Chaves et al 2018;Godoy et al 2018;Meireles and Manos 2018;Zenk et al 2018). Thus, the present study aimed to test the cross-amplification of nuclear microsatellite markers, originally designed for other bromeliad species, in Aechmea distichantha.…”
Section: Introductionmentioning
confidence: 97%
“…Accordingly, the level of transferability obtained for the species studied here can be considered above average, since 12 of the 24 pairs of primers tested (50%) yielded positive results. Similarly successful results in marker transfer have also been reported for other species of Bromeliaceae (Barbará et al 2007a;Paggi et al 2008;Palma-Silva et al 2009Wöhrmann and Weising 2011;Zanella et al 2012;Goetze et al 2013;Lavor et al 2014;Neri et al 2015;Ferreira et al 2017;Pereira et al 2017;Chaves et al 2018;Godoy et al 2018Godoy et al , 2019Zenk et al 2018). High transferability between species of the same Bromeliaceae subfamily is probably due to the family's large adaptive radiation, leading to low levels of divergence in their DNA sequences (see Palma-Silva et al 2006;Barbará et al 2007b).…”
Section: Resultsmentioning
confidence: 70%